Secondary students’ attitude towards mathematics in a selected school of Maldives - Mohamed, Lawsha; Waheed, Hussain (Centre for Promoting Ideas, USA, 2011)
Students’ attitude towards mathematics has been a factor that is known to influence students’ achievement in mathematics. The purpose of this study is to find out the students attitude towards mathematics and find out gender difference in attitude towards mathematics in a selected school of Maldives. A total of 200 secondary students were administered with a questionnaire to find out their attitudes towards mathematics. The students answered questions regarding their personal confidence to mathematics and perceived usefulness of mathematics. The results show that the students’ positive attitude towards mathematics is medium and there is no gender difference in their attitudes.